Quantum tunneling and quasinormal modes in the spacetime of the Alcubierre warp drive - Jusufi, Kimet; Sakalli, Izzet; Övgün, Ali (Springer/Plenum Publishers, 2018)
In a seminal paper, Alcubierre showed that Einstein's theory of general relativity appears to allow a super-luminal motion. In the present study, we use a recent eternal-warp-drive solution found by Alcubierre to study the effect of Hawking radiation upon an observer located within the warp drive in the framework of the quantum tunneling method. We find the same expression for the Hawking temperatures associated with the tunneling of both massive vector and scalar particles, and show this expression to be proportional to the velocity of the warp drive. On the other hand, since the discovery of gravitational waves, the quasinormal modes (QNMs) of black holes have also been extensively studied. With this purpose in mind, we perform a QNM analysis of massive scalar field perturbations in the background of the eternalAlcubierre- warp-drive spacetime. Our analytical analysis shows that massive scalar perturbations lead to stable QNMs.
Keywords: Warp drive; Super-luminal motion; Alcubierre; Hawking radiation; Quasinormal modes; Scalar; Massive vector particles